2022
DOI: 10.1371/journal.pone.0273385
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-(3–4) normalizes the elevated arterial blood pressure and abnormal Na+/energy handling associated with chronic undernutrition by counteracting the effects mediated by type 1 angiotensin II receptors

Abstract: We investigated the mechanisms by which chronic administration of a multideficient diet after weaning alters bodily Na+ handling, and culminates in high systolic blood pressure (SBP) at a juvenile age. From 28 to 92 days of age, weaned male Wistar rats were given a diet with low content and poor-quality protein, and low lipid, without vitamin supplementation, which mimics the diets consumed in impoverished regions worldwide. We measured food, energy and Na+ ingestion, together with urinary Na+ excretion, Na+ d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 54 publications
3
12
0
Order By: Relevance
“…Figure 7 shows the opposite influence of the nutritional status and rostafuroxin administration on the two Na + -transporting ATPases present in the basolateral membranes of proximal tubule cells [16]. The activity of the main pump, the ouabain-sensitive (Na + +K + )ATPase (Figure 7A), decreased by 30% in RBD rats in comparison to CTRL, as previously described [17], with rostafuroxin promoting a further decrease in both groups. In the case of the ouabain-resistant, furosemide-sensitive Na + -ATPase (Figure 7B), undernutrition provoked a 50% increment in its activity, equalized at the same higher levels in CTRL+Rosta and RBD+Rosta after further upregulation in the animals given the drug.…”
Section: Na + -Transporting Atpases From Proximal Tubule Cells and Sy...supporting
confidence: 59%
See 3 more Smart Citations
“…Figure 7 shows the opposite influence of the nutritional status and rostafuroxin administration on the two Na + -transporting ATPases present in the basolateral membranes of proximal tubule cells [16]. The activity of the main pump, the ouabain-sensitive (Na + +K + )ATPase (Figure 7A), decreased by 30% in RBD rats in comparison to CTRL, as previously described [17], with rostafuroxin promoting a further decrease in both groups. In the case of the ouabain-resistant, furosemide-sensitive Na + -ATPase (Figure 7B), undernutrition provoked a 50% increment in its activity, equalized at the same higher levels in CTRL+Rosta and RBD+Rosta after further upregulation in the animals given the drug.…”
Section: Na + -Transporting Atpases From Proximal Tubule Cells and Sy...supporting
confidence: 59%
“…In a recent study [17] and here (Figure 7A,B) we demonstrated that chronic undernutrition provoked by the continued administration of RBD to male rats downregulates the ouabain-sensitive (Na + +K + )ATPase and upregulates the ouabain-resistant Na + -ATPase, the two Na+-transporting ATPases that are responsible for the proximal renal reabsorption of more than 70% of the Na + filtered in the glomeruli [46,47]. Even though the hydrolytic activity of (Na + +K + )ATPase in membrane preparations does not quantitatively reflect the transport stoichiometry in intact cells, it is possible to propose that less bulk Na + is reabsorbed in these tubules in undernourished rats because the lower transport demand in lower-sized animals.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In the case of RBD undernourished rats, the cortical renal tubulointerstitium has more than four times the number of angiotensin II‐positive cells found in CTRL rats (Silva, Muzi‐Filho, et al, 2014), evidence of an increased tissular RAAS activity. Moreover, rostafuroxin‐sensitive hypertension they develop (Figure 8) is also completely normalized by the administration of losartan (Pereira‐Acácio et al, 2022), an antagonist of type 1 angiotensin II receptors (Timmermans et al, 1995), suggesting an interaction between rostafuroxin and RAAS. In terms of actions in vessels (such as the thoracic aorta and mesenteric arteries), rostafuroxin appears to have opposite effects and the same final targets as RAAS.…”
Section: Discussionmentioning
confidence: 98%